Transport of Moving Duck Flocks in Indonesia and Vietnam: Management Practices That Potentially Impact Avian Pathogen Dissemination - Khaw, Shan Wen Stacy; Vu, Le Tri; Yulianto, Didik; Meers, Joanne; Henning, Joerg (Frontiers in Veterinary Science, 2021)
Highly pathogenic avian influenza (HPAI) virus is endemic in Indonesia and Vietnam, where ‘moving’ duck production is commonly practiced. Questionnaire surveys were conducted with transporters of ‘moving’ duck flocks in Indonesia (N=55) and Vietnam (N=43). The main purpose of transportation was to transport duck flocks between rice paddies used for scavenging. Trucks were commonly utilized for transport in both countries (Indonesia: 98.2%, 54/55; Vietnam: 37.2%, 16/43), while boats were only used in Vietnam (62.8%, 27/43). Transporters in Vietnam moved larger flocks and travelled over longer distances. Deaths of ducks due to diseases were reported in both countries (Indonesia: 16.4%, 9/55; Vietnam: 4.7%, 2/43; p=0.11). Throwing away of carcasses was the primary method of disposal of dead birds in Indonesia (60.0%, 33/55), but was not practiced in Vietnam (p<0.001), while more transporters in Vietnam (34.9%, 15/43) buried carcasses compared to Indonesia (6.8%, 4/55; p=0.001). Consumption of carcasses (20.9%, 9/43), sale of dead ducks (14.0%, 6/43) and processing of ducks for fish feed (9.3%, 4/43) was conducted in Vietnam, but not in Indonesia. Vehicles were predominantly cleaned in rivers and stored outside in Vietnam, while cleaning and storage was usually conducted in houses/garages in Indonesia. Management practices that potentially enhance HPAI virus dissemination in Indonesia were related to multipurpose usage of transport vehicles and disposal of birds in the environment, while unsafe practices in Vietnam relate to the mixing of birds during transport, the processing of dead carcasses and the storage and cleaning of transport vehicles.